Optimization of Sensing Receiver for Cognitive Radio Applications. (2nd September 2009) - Zamat, Hassan; Natarajan, Balasubramaniam
Abstract : We propose an optimized dedicated broadband sensing receiver architecture for use in cognitive radios supporting delay sensitive applications. Specifically, we first reason the need for a dedicated sensing receiver that employs a combination of coarse and fine scanning to reduce sensing time over a large bandwidth. We derive an expression for mean acquisition/detection time as a function of a number of parameters including the number of coarse and fine frequency bins employed. We then determine the optimal number of coarse and fine bins that minimize the overall detection time required to identify idle channels under various system conditions. Using analytical and simulation results, we quantify the dependence of optimal coarse and fine bin selection on system parameters such as (1) size of FFT used in scanning; (2) probability of detection and false alarm of the underlying sensing algorithm; (3) signal-to-noise ratio of the received signal, and (4) expected number of available channels. The primary contribution of this work lies in a practical realization of an optimal broadband sensing receiver.